Firm digitalisation and mobility - Do Covid-19-related changes persist? - Janna Axenbeck; Irene Bertschek; Patrick Breithaupt; Daniel Erdsiek (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
The Covid-19 pandemic has sparked hope that firm digitalisation will result in long-lasting reductions in mobility and related carbon missions via the use of working from home and online services. In this study, we quantify the extent to which firm digitalisation can be associated with changes in mobility during the Covid-19 crisis in Germany, both when strong restrictions were in place and after the restrictions were lifted. To this end, we employ a novel text-mining approach to measure digitalisation based on firm websites. We aggregate our firm digitalisation indicator at the district level and link it to changes in mobility between January 2020 and December 2022. Our results indicate that districts with a higher level of firm digitalisation experienced a stronger reduction in mobility during the first two years of the pandemic. However, mobility almost came back to pre-crisis levels after most restrictions were lifted, suggesting that environmental improvements are not long-lasting.
Keywords: H12; I12; L96; O18; 330; Covid-19; digitalisation; mobility reductions; environmental improvements